2017
DOI: 10.1016/j.anifeedsci.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the postruminal methionine requirement of growing lambs by using the indicator amino acid oxidation technique

Abstract: Methionine was demonstrated to be the most limiting amino acid for growing sheep when microbial protein is the predominant source of absorbable AA, but its specific requirement was not well quantified. The indicator amino acid oxidation (IAAO) method is based on the concept that when the most limiting amino acid (LAA) is deficient for protein synthesis, then all other AAs will be oxidized. With increasing intakes of the LAA, IAAO will decrease until the requirement for the LAA is met, and there is no further c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…When adequate energy is available, protein deposition shows a linear relationship with the supply of the most limiting AA, until another AA becomes more limiting [43]. Inconsistent results have been reported regarding the ability of RPM supplementation to render Met available for absorption in the small intestine [44,45]. However, the present study showed that Met was absorbed, which affected the utilisation of other AAs.…”
Section: Discussionmentioning
confidence: 40%
“…When adequate energy is available, protein deposition shows a linear relationship with the supply of the most limiting AA, until another AA becomes more limiting [43]. Inconsistent results have been reported regarding the ability of RPM supplementation to render Met available for absorption in the small intestine [44,45]. However, the present study showed that Met was absorbed, which affected the utilisation of other AAs.…”
Section: Discussionmentioning
confidence: 40%
“…This less invasive approach was further supported in a following study (9) in which identical lysine requirement estimates were found in humans repeatedly fed 13 C-Phe or intravenously supplied 13 C-Phe. Since then, the IAAO technique has been broadly used under different states of health (10)(11)(12) and in different species (13)(14)(15)(16)(17) due to its noninvasive and highly sensitive nature.…”
Section: Introductionmentioning
confidence: 99%